The Lazy Teacher's Handbook - New Edition: How your students learn more when you teach less - Smith, Jim; Gilbert, Ian (Crown House Publishing La Vergne, 2017)
It's more than six years since the bestselling Lazy Teacher's Handbook was first published and Jim Smith's Lazy Teaching philosophy has developed significantly in that time. This new revised edition details Jim's latest thinking on how to be the best lazy, but outstanding, teacher you can be.